Single-step template synthesis of mesoporous silicas containing thiourea functional groups - Zub, Yu.L.; Gona, O.I.; Chuiko, A.A.; Yaroshenko, N.A.; Dabrowski, A. (Functional Materials, 2006)
Mesopo rous adsorbents co ntaining mono-(-(CH₂)₃NHC(=S)NHC₂H₅) or bi-(-(CH₂)₃NHC(=S)NHC₂H₅ / amino) functional surface layer have been synthesized in a single-step process using bi- or tricomponent (with respect to alkoxysilanes) systems and
1-dodecylamine as a template. The studied systems have been shown to have a disordered lattice similar to hexagonal one, a developed porous structure (Sₛₚ 409 to 718 m²/g; Vₛ 0.26 to 0.82 сm³/g; d 2.4 to 2.5 nm) and a relatively high content of functional groups (Cc=s from 0.7 mmol/g to 2.2 mmol/g). It has been found that hydrothermal treatment of mesophases in a mother liquor for 24 hours at 80 ℃ does not result in an enhanced structure ordering but even in worsened structure-adsorption characteristic of the final products. Мезопористi а Д сорбенти, що мiстять моно-((CH₂)₃NHC(=S)NHC₂H₅) чи бi- (- NНС(=S)NНC₂H₅/амiн) функцiональний поверхневий шар, одностадiйно синтезовано з використанням дво- чи трикомпонентних (за алкоксисиланами) систем i 1-додециламiна як темплату. Показано, що вони мають неупорядковану гратку, близьку до гексагональної, розвинуту порувату структуру (Sₙᵤₘ - 409-718 м²/Г, V = 0.26-0.82 см³/Г, d = 2.4-2.5 нм) та вiдносно високий вмiст функцiональних груп (Сc=s вiд 0.7 ммоль/Г до 2.2 ммоль/Г). Встановлено, що гiдротермальна обробка мезофаз у маточному розчинi протягом 24 годин при 80 ℃ не тiльки не веде до бiльш впорядкованої структури, а навiть дещо погiршуе структурно-адсорбцiйнi характеристики кiнцевих продуктiв. Мезопористые адсорбенты, содержащие моно-(-(CH₂)₃NHC(=S)NHC₂H₅) или би-(-(CH₂)₃NHC(=S)NHC₂H₅)/амин) функциональный поверхностный слой, одностадийно синтезированы с использованием двух- или трёхкомпонентных (по алкоксисиланам)
систем и 1-додециламина как темплата. Показано, что они имеют неупорядоченную решётку, близкую к гексагональной, развитую пористую структуру (Sуд 409-718 м²/г, Vc 0.26-0.82 см³/г, d 2.4-2.5 нм) и относительно высокое содержание функциональных групп (Сc=s - от 0.7 ммоль/г до 2.2 ммоль/г). Установлено, что гидротермальная обработка мезофаз в маточном растворе в течение 24 ч при 80 ℃ не только не ведёт к более упорядоченной структуре, но даже несколько ухудшает структурно-адсорбционные характеристики конечных продуктов.